Comparative Study of Newar And Japanese Classifiers - Shrestha, Arun (Tribhuvan University Journal, 2010)
This paper compares and contrasts the numeral classifier systems of two genetically unrelated languages: Newar of Kathmandu and “Hyoujungo”, Japanese spoken in Tokyo, the defacto official language of Japan. It is not the case either in Newar or in Japanese that  nouns in general can be directly quantified by a number. For example, in Newar one cannot say*ni che two house ‘Two houses” for ‘two houses’. Rather, one must say ni-khache ‘two-CL house” Two houses” .The noun che ‘house’ requires that the numeral classifier -kha be affixed to numerals used for counting houses. One might say that che ‘house’ is not conceived of as a separate countable entity. Only when the unit -kha ‘CL’ is suffixed to the number do we have a countable entity. Numeral classifiers: The choice of noun determines the choice of classifier both in Newari and in Japanese. By looking at the nouns associated with a given classifier it is possible to identify the way in which a noun selects its classifier. In Newar there are three different ways in which nouns select their classifiers (1) according to semantic parameters (as when sentient nouns select the classifier -mha, (2) by unique lexical collocation (as when che ‘house’ selects -kha ‘CL’) and (3) by full or partial reduplication (as when ha: ‘leaf’ selects thehead noun ha: itself, where as salakhwa: ‘horse’s hoof’ selects -khwa:, only thelatter portion of the head noun (Hale 2005).These modes can be taken as the basis for a three-term typology of classifier selection: (1) semantic selection, (2) lexical selection, and (3)morphological selection. This paper provides a detailed comparison of  Newar and Japanese classifiers within each of these three types of selection. Though all three types are attested in each language, there are mutual counterparts and skewing between the two languages.